Internal Jugular Vein as Alternative Access for Implantation of a Wireless Pulmonary Artery Pressure Sensor. (August 2019) - Abraham, Jacob; McCann, Patrick; Wang, Lian; Schnell Heringer, Amanda; Paulsen, Jeff; Chappell, Jay; Remick, Joshua; Westerdahl, Daniel; Lewis, Rebecca; Callis, Katherine; Spinelli, Kateri J.; Klein, Liviu
Abstract : Background: A wireless pulmonary artery pressure sensor (CardioMEMS) is approved for implantation via the femoral vein. The internal jugular vein (IJ) is an attractive alternative access route commonly used in pulmonary artery catheterization. Methods and Results: Retrospective chart review was performed for all sensor implants from 10 providers at 4 centers from September 2016 to June 2018. To compare procedural outcomes and discharge efficiency between groups, multivariate analyses incorporating potential confounders were performed. Seventy-three (28%) patients had femoral access, and 189 (72%) had IJ access; demographics were similar between the groups. Complications, including one case of hematoma and 4 cases of mild hemoptysis, and 30-day mortality (2%–3%) did not differ between groups. Provider preference for IJ access substantially increased over time, with IJ accounting for 90% of cases in 2018. After risk-adjustment, IJ cases had 20% (5%–33%) shorter fluoroscopy time ( P =0.01) and 24% (7%–38%) lower contrast volume ( P =0.008). Compared with outpatient femoral cases, outpatient IJ cases had 62% (52%–69%) faster needle-to-door time and were 34 times (6–235) more likely to have same-day discharge ( P <0.001 for both). Conclusions: IJ access for CardioMEMS implant is a safe alternative associated with superior procedural and discharge outcomes. Implanters at 4 high-volume centers adopted IJ access as the preferred implant approach. Abstract : Supplemental Digital Content is available in the text.